An outer shade of Pal: abundance analysis of the outer halo globular cluster Palomar 13 - Koch-Hansen, Andreas; Côté, Patrick (Astronomy and astrophysics, 2019)
At a Galactocentric distance of 27 kpc, Palomar 13 is an old globular cluster (GC) belonging to the outer halo. We present a chemical abundance analysis of this remote system from high-resolution spectra obtained with the Keck/HIRES spectrograph. Owing to the low signal-to-noise ratio of the data, our analysis is based on a coaddition of the spectra of 18 member stars. We are able to determine integrated abundance ratios for 16 species of 14 elements, of α-elements (Mg, Si, Ca, and Ti), Fe-peak (Sc, Mn, Cr, Ni, Cu, and Zn), and neutron-capture elements (Y and Ba). While the mean Na abundance is found to be slightly enhanced and halo-like, our method does not allow us to probe an abundance spread that would be expected in this light element if multiple populations are present in Pal 13. We find a metal-poor mean metallicity of −1.91 ± 0.05 (statistical) ±0.22 (systematic), confirming that Pal 13 is a typical metal-poor representative of the outer halo. While there are some differences between individual α-elements, such as halo-like Mg and Si versus the mildly lower Ca and Ti abundances, the mean [α/Fe] of 0.34 ± 0.06 is consistent with the marginally lower α component of the halo field and GC stars at similar metallicity. We discuss our results in the context of other objects in the outer halo and consider which of these objects were likely accreted. We also discuss the properties of their progenitors. While chemically, Pal 13 is similar to Gaia-Enceladus and some of its GCs, this is not supported by its kinematic properties within the Milky Way system. Moreover, its chemodynamical similarity with NGC 5466, a purported progeny of the Sequoia accretion event, might indicate a common origin in this progenitor. However, the ambiguities in the full abundance space of this comparison emphasize the difficulties in unequivocally labeling a single GC as an accreted object, let alone assigning it to a single progenitor.
Gesehen am 11.02.2020